Napping and heart rate variability in elite athletes - Souabni, M.; Souabni, M. J.; Hidouri, S.; Ammar, A.; Younes, M.; Hammouda, O.; Driss, T. (Biology of Sport, 2024)
Sleep and autonomic nervous system (ANS) influence each other in a bidirectional fashion. Importantly, it has been proposed that sleep has a beneficial regulatory influence over cardiovascular activity, which is mostly controlled by autonomic regulation through the activity of sympathetic and parasympathetic pathways of the ANS. A well-established method to non-invasively assess cardiac autonomic activity is heart rate variability (HRV) analysis. We aimed to investigate the effect of a 40-min nap opportunity on HRV. Twelve professional basketball players randomly accomplished two conditions: 40-min nap (NAP) and control (CON). Nocturnal sleep and naps were monitored by actigraphic recording and sleep diaries. Total sleep time (TST), time in bed (TIB), sleep efficiency (SE), sleep onset latency (SOL), and wake after sleep onset (WASO) were analyzed. HRV was analyzed in 5-min segments during quiet wake before and after each condition with controlled breathing. Were analysed high (HF) and low frequency (LF) bands, the standard deviation of NN interval (SDNN), HRV index and stress index (SI). Wellness Hooper index and Epworth Sleepiness Scale (ESS) were assessed before and after both conditions. There was no significant difference in TIB, TST, SE, WASO, and VAS between NAP and CON. A significant increase in SDNN, HRV index, and LF and a significant decrease in HF, SI, ESS, and Hooper`s stress and fatigue scores were observed from pre- to post-nap. In conclusion, napping reduces sleepiness, stress and fatigue, and might provide an advantage by preparing the body for a much-required sympathetic comeback following peaceful rest.